Implementation of Business Ethics in Snack Buying and Selling Practices at TB MART from a Sharia Economic Perspective - M.Khoirul Mustofa (JURNAL ECONOMINA, 2026)
This study aims to analyze in depth the implementation and exploration of Islamic business ethics in the practice of buying and selling in a modern retail organization at TB MART Darussalam, Indonesia, in order to mitigate the discrepancy between the theological norms of Islamic economics and the reality of contemporary market behavior. Using a qualitative approach with a case study type, data were collected through in-depth interviews, participant observation, documentation, and audio analysis of 6 informants including store managers, cashiers, sales assistants, and regular customers. The results of the study indicate that TB MART Darussalam has successfully internalized Islamic norms into its organizational social structure so that business ethics manifests as automatic behavior (habitualization). This actualization is evidenced through three main operational aspects: first, the implementation of quality transparency (tabyin) in the form of providing "Honest Discount Racks" for minor defective products or products nearing their expiration date to reduce information asymmetry (gharar); second, the guarantee of halal thayyiban products through strict screening of official halal certification (MUI/BPJPH) from suppliers; and third, structured quality control management through weekly stocktaking to remove damaged products from display shelves. The strong synergy between internal management monitoring based on the values ​​of amanah (trustworthiness) and siddiq (trustworthiness), and consumer self-monitoring has proven successful in eliminating doubts (syubhat), creating a sense of security, fostering trust, and building long-term customer loyalty amidst competition.